Corrigendum: real-world management of abnormal scarring using topical silicone gel: expert consensus and case series from the Asian SCARS Expert Group - Xiaonan Yang; Visnu Lohsiriwat; Frank Chun Shin Chang; Tan Thiam Chye; Catherine J Howard; Liang Qiao; Steven W Shaw; Tu Nguyen Anh Tran; Chan Yung; Daniel Dellosa; Dinesh Nagrale (BioExcel Publishing Ltd, 2023)
The authors wish to make the following corrections to their article: Yang X, Lohsiriwat V, Chang FCS, Chye TT, Howard CJ, Qiao L, Shaw SW, Tran TNA, Yung C, Dellosa D, Nagrale D. Real-world management of abnormal scarring using topical silicone gel: expert consensus and case series from the Asian SCARS Expert Group. Drugs Context. 2023;12:2023-4-3. https://doi.org/10.7573/dic.2023-4-3